Accessing support and empowerment online: The experiences of individuals with diabetes. (18th July 2017) - Brady, Ellen; Segar, Julia; Sanders, Caroline
Abstract: Context: The use of the internet for health information by those with long‐term conditions is growing. It has been argued that this represents a form of empowerment by patients, as it enables them to control the content and flow of the information available to them. To explore this, the use of online discussion groups by those with diabetes was examined. Method: Semi‐structured interviews were conducted with 21 participants with type 1 and 2 diabetes and analysed using thematic analysis. Participants were recruited via online and offline routes, namely discussion boards, newsletters, and research networks related to diabetes. Results: By drawing on the advice, information, and support shared online, participants were empowered to position themselves as active participants in their own health care and to further engage with health‐care professionals. Conclusion: The findings indicate that forums can play a valuable role in aiding and motivating individuals in the daily management diabetes and highlight how this support is used to complement formal health services. However, more work needs to be carried out to determine to explore when and under what circumstances online support may be particularly beneficial to those with long‐term conditions.